Real-Time Transmission and Storage of Video, Audio, and Health Data in Emergency and Home Care Situations. (7th May 2007) - Barbieri Barbieri, Ivano Ivano; Lambruschini Lambruschini, Paolo Paolo; Raggio Raggio, Marco Marco; Stagnaro Stagnaro, Riccardo Riccardo
Abstract : The increase in the availability of bandwidth for wireless links, network integration, and the computational power on fixed and mobile platforms at affordable costs allows nowadays for the handling of audio and video data, their quality making them suitable for medical application. These information streams can support both continuous monitoring and emergency situations. According to this scenario, the authors have developed and implemented the mobile communication system which is described in this paper. The system is based on ITU-T H.323 multimedia terminal recommendation, suitable for real-time data/video/audio and telemedical applications. The audio and video codecs, respectively, H.264 and G723.1, were implemented and optimized in order to obtain high performance on the system target processors. Offline media streaming storage and retrieval functionalities were supported by integrating a relational database in the hospital central system. The system is based on low-cost consumer technologies such as general packet radio service (GPRS) and wireless local area network (WLAN or WiFi) for lowband data/video transmission. Implementation and testing were carried out for medical emergency and telemedicine application. In this paper, the emergency case study is described.